Parasitic infections in Malaysia-review of the last millennium - Khairul Anuar, A.; Fong, M.Y.; Init, I. (2001)
As Malaysia marches into the new millenium with aspirations to be a fully developed nation, the health and well being of its people remains a top priority in the agenda. Among others, control or eradication of infectious diseases that affects large segments of the population has been given much attention. Significant manpower and finance have been channeled into these efforts. Diseases caused by parasitic infections have always been a major concern among health providers and managers in Malaysia. Historically, when the Institute for Medical Research (IMR) was established in Kuala Lumpur in 1899, the instituteâs top priorities were to conduct research into parasitology, diagnosis, treatment and control of malaria. Since then, many other parasites and related diseases have been investigated. In fact, some of the pioneer researches such as on filariasis, malaria, helminthiasis and scrub typhus have been conducted in Malaysia and their contribution in the control of these diseases have been immense.This paper presents a review on the epidemiology and status of the major parasitic infections in the country. It is hoped that the data and views presented in this review will be useful as a guide for the future planning of measures in the combating of parasitic infections in Malaysia.